Remediation and Respect: Do Remediation Technologies Alter Our Responsibility?. (1st November 2009) - Hale, Benjamin; Grundy, W.P.
Abstract : In this paper we examine the relation between technologies that aim to remediate pollution and moral responsibility. Contrary to the common view that successful remediation technologies will permit the wheels of industry to turn without interruption, we argue that such technologies do not exculpate polluters of responsibility. To make this case, we examine several environmental and non-environmental cases. We suggest that some strategies for understanding the moral problem of pollution, and particularly those that emphasise harms, exclude an important dimension of morality. In lieu of these strategies, we employ the concept of respect to characterise the type of attitude that underlies many of our judgments about responsibility.